PERAN GURU DALAM IMPLEMENTASI PENDEKATAN ETNOPEDAGOGI PADA PEMBELAJARAN SENI BUDAYA DI SMA KOTA MAKASSAR - Rahma M (JURNAL IMAJINASI, 2026)
This study aims to analyze the role of teachers in implementing the ethnopedagogical approach in cultural arts learning at senior high schools in Makassar. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation studies. The research subjects consisted of arts teachers and students from several schools, namely SMAN 3 Makassar, SMAN 5 Makassar, SMAN 8 Makassar, and SMAN 9 Makassar. The results indicate that cultural arts learning has begun to reflect ethnopedagogical principles, particularly in integrating local cultural values into the learning process. However, teachers' understanding of ethnopedagogy in lesson planning remains limited. Culture-based learning has been proven to enhance students' cultural identity awareness, foster pride in local heritage, and strengthen character development. Therefore, strengthening teacher competencies and developing supportive educational policies are necessary to ensure systematic and sustainable implementation of ethnopedagogy.